Psychometric validation of the 15-item Questionnaire about the Process of Recovery in Spain (QPR-15-SP) - Goodman-Casanova, Jessica Marian; Cuesta-Lozano, Daniel; Alupoaei, Catalina; Grasa Bello, Eva María; Herrera-Imbroda, Jesús; Mayoral-Cleries, Fermin; Guzman-Parra, Jose (Frontiers in Psychology, 2023)
Reliable and valid instruments are needed to measure the impact of mental health services and programs on the journeys of recovery of service users. The aim of this study was to explore the psychometric properties of the cross-culturally adapted 15-item Questionnaire about the Process of Recovery in Spain (QPR-15-SP). One hundred and ten participants from three locations in Spain (Málaga, Barcelona and Madrid), who were users of primary and specialized mental health services, were interviewed from October 2021 to June 2022. The internal consistency obtained was excellent: ω =.93 and α =.92. Temporal reliability using intraclass correlation coefficients was moderate (ICC=.684, P<.000). Regarding convergent validity, the QPR-15-SP had a moderate correlation with the Clinical Outcomes in Routine Evaluation-Outcome Measure (CORE-OM) (ρ=-.500, P<.000), a Visual Numeric Recovery Scale (VNRS) (ρ=.591, P<.000), and the Stages of Recovery Instrument (STORI) (r=.566, P<.000). Correlations between advanced stages of recovery and higher QPR-15-SP scores were found (Moratorium: ρ =-.579, P<.000; Awareness: ρ =-.130, P=.189; Preparation: r=-.043, P=.665; Rebuilding: r=.460, P<.000; Growth: ρ =.697, P<.000). In terms of divergent validity, the QPR-15-SP had low correlation with the DUKE-UNC Functional Social Support Scale (ρ=.273, P<.005). The confirmatory factor analysis of the 1-factor structure obtained reasonable goodness of fit indexes. The QPR-15-SP has acceptable psychometric properties, providing support for measuring recovery in Spain and allowing international comparison research.